2017
DOI: 10.1098/rsif.2017.0376
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty, epistemics and active inference

Abstract: Biological systems—like ourselves—are constantly faced with uncertainty. Despite noisy sensory data, and volatile environments, creatures appear to actively maintain their integrity. To account for this remarkable ability to make optimal decisions in the face of a capricious world, we propose a generative model that represents the beliefs an agent might possess about their own uncertainty. By simulating a noisy and volatile environment, we demonstrate how uncertainty influences optimal epistemic (visual) forag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
252
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 205 publications
(260 citation statements)
references
References 69 publications
8
252
0
Order By: Relevance
“…In two-state DCM, this gain modulation arises from the excitation/inhibition balance of excitatory pyramidal cells and inhibitory interneurons. This interpretation entails that, besides generating prediction error signals, melodic deviants are afforded a higher precision than standards, which is consistent with the role of salient stimuli in the orientation of attention (Polich and Criado, 2006;Hannon and Trainor, 2007;Parr and Friston, 2017) . Thus, unexpected sounds would point to the sources in the auditory scene that are most informative and relevant and need to be prioritized for processing through gain mechanisms.…”
Section: Discussionsupporting
confidence: 58%
“…In two-state DCM, this gain modulation arises from the excitation/inhibition balance of excitatory pyramidal cells and inhibitory interneurons. This interpretation entails that, besides generating prediction error signals, melodic deviants are afforded a higher precision than standards, which is consistent with the role of salient stimuli in the orientation of attention (Polich and Criado, 2006;Hannon and Trainor, 2007;Parr and Friston, 2017) . Thus, unexpected sounds would point to the sources in the auditory scene that are most informative and relevant and need to be prioritized for processing through gain mechanisms.…”
Section: Discussionsupporting
confidence: 58%
“…Pupillary responses, because of their relation to the noradrenergic system [71], have previously been linked to unexpected uncertainty [27,84], sometimes taken as synonym to surprise [7,28,6] and sometimes as an equivalent of volatility, i.e. how likely the environment dynamics is to change [84,27,21,85,86,87]. These two definitions are strongly related since surprising observations suggest that the statistical structure of the environment may have changed [88].…”
Section: Relation To Alternative Theoriesmentioning
confidence: 99%
“…While surprise is event-related and could be linked to phasic pupillary changes [28], volatility varies slowly and could be related to tonic pupil size [27]. Unexpected uncertainty relates also strongly to the problem of exploitation/exploration trade-off, another concept linked to pupillary responses [30,29,83,89]: when confidence in the internal model of the environment drops following surprising observations, exploitation strategies lose value with respect to alternative exploration strategies [84]. However, recent data has shown that variations of tonic pupil size are not indicative of unexpected uncertainty, but are rather a signature of reducible uncertainty (ambiguity resulting from poor model of environment, caused by undersampling; Krishnamurthy et al [21]) or expected uncertainty (related to the variance of the task; De Berker et al [12]).…”
Section: Relation To Alternative Theoriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in precision were implemented via a temperature parameter of a softmax function applied to a fully precise version of likelihood mappings between emotion concepts and the 5 types of lower-level information that the agent could attend to (where a higher value indicates higher precision). For a more technical account of this type of manipulation, please see (Parr & Friston, 2017a). under different levels of precision for two parameters (denoted by temperature values for a softmax function controlling the specificity of the A and B matrices for hidden state factor 1; higher values indicate higher precision).…”
Section: Simulating Emotions 26mentioning
confidence: 99%